The Influence of Pricing And Promotion on Satisfaction Through Purchasing Decisions as A Study Intervening Variable at PT Hotel Kampung Sampireun - Tojiri, Yusuf; Rusdian, Suca; Sugiat, Jajang (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: This research aims to investigate the influence of price and promotion on purchasing decisions and their impact on consumer satisfaction at PT. Kampung Sampireun Resort and Spa. The issues raised focus on how price and promotions contribute to consumer purchasing decisions, as well as how these purchasing decisions influence the level of consumer satisfaction. With increasing competition in the hotel industry, these resorts need to understand the factors that can influence consumer decisions and increase their satisfaction. Methodology: The research method used is correlation analysis, with data collected through questionnaires from respondents who are consumers or potential consumers of this resort. Finding: The research results show that both price and promotion have a significant influence on purchasing decisions, although the resulting correlation coefficient is categorized as low. Purchasing decisions also act as a mediator between price, promotion, and consumer satisfaction variables, indicating that a good strategy in setting prices and promotions can contribute to increasing customer satisfaction. Conclusion: The strategic implications of this research suggest the need for these resorts to continue to optimize pricing and promotion strategies and consider additional factors such as service quality and user experience to achieve more holistic consumer satisfaction. Recommendations for future research include exploring additional factors that may influence consumer satisfaction as well as testing the effectiveness of more complex marketing strategies. Overall, this research provides a strong basis for PT. Kampung Sampireun Resort and Spa to develop more effective marketing strategies to increase competitiveness and maintain customer satisfaction in the future.